2013
DOI: 10.1248/bpb.b12-00711
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMP-Activated Protein Kinase by a Plant-Derived Dihydroisosteviol in Human Intestinal Epithelial Cell

Abstract: Our previous study has shown that dihydroisosteviol (DHIS), a derivative of stevioside isolated from Stevia rebaudiana (Bertoni), inhibits cystic fibrosis transmembrane conductance regulator (CFTR)-mediated transepithelial chloride secretion across monolayers of human intestinal epithelial (T84) cells and prevents cholera toxin-induced intestinal fluid secretion in mouse closed loop models. In this study, we aimed to investigate a mechanism by which DHIS inhibits CFTR activity. Apical chloride current measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…NOX4 is expressed in pulmonary fibroblasts and targeting of NOX4 inhibited the fibrotic process in experimental PF (Chan et al, 2009; Hecker et al, 2009). AMPK is a metabolic regulator, the activation of it exhibits improvement in metabolic disorders and prevention of organ dysfunction during pulmonary diseases (Myerburg et al, 2010; Muanprasat et al, 2013; Zhao et al, 2014; Malik et al, 2015). What’s more, several studies have demonstrated that activation of AMPK effectively inhibited the over-expression of NOX4 in activated lung fibroblasts (Park et al, 2012; Jian et al, 2013; Li et al, 2015; Lu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…NOX4 is expressed in pulmonary fibroblasts and targeting of NOX4 inhibited the fibrotic process in experimental PF (Chan et al, 2009; Hecker et al, 2009). AMPK is a metabolic regulator, the activation of it exhibits improvement in metabolic disorders and prevention of organ dysfunction during pulmonary diseases (Myerburg et al, 2010; Muanprasat et al, 2013; Zhao et al, 2014; Malik et al, 2015). What’s more, several studies have demonstrated that activation of AMPK effectively inhibited the over-expression of NOX4 in activated lung fibroblasts (Park et al, 2012; Jian et al, 2013; Li et al, 2015; Lu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the improvement in physical performance, induced by the addition of S. rebaudiana to the whey protein supplement, maybe due to other mechanisms than its antioxidant activity. Recent studies have shown that compounds extracted from the leaves of S. rebaudiana stimulate the activation of AMPK, which has an important role during exercise [35, 36]. However, this protein seems to be preferentially activated by endurance, rather than resistance, exercise [37].…”
Section: Discussionmentioning
confidence: 99%
“…Activated AMPK in turn mediated an increase in Caudal type homebox 2 (CDX2) expression, which in turn is a transcriptional factor responsible for intestinal epithelial cells differentiation [ 65 ]. AMPK is an energy metabolism regulator having an important role in maintaining metabolic homeostasis [ 66 , 67 ]. It influences the epithelial barrier by differentiating, forming and maintaining it.…”
Section: Nutraceuticalsmentioning
confidence: 99%